The why of consumption : contemporary perspectives on consumer motives, goals, and desires - Ratneshwar, S.; Mick, David Glen; Huffman, Cynthia (Routledge, 2003)
This book brings together an international collection of authors from a variety of disciplines who offer new and critical perspectives, summarize key findings and provide important theoretical frameworks to guide the reader through the 'why?' of consumption. The book answers questions such as: What is the nature of motives, goals, and desires that prompt consumption behaviours? Why do consumers buy and consume particular products, brands and services from the multitude of alternatives afforded by their environments? How do consumers think and feel about their cravings? Unique in focus and with multifaceted approach which anyone interested in consumption and consumer research will find fascinating, this topical book provides an excellent overview of current research, and imparts key insights to illuminate the subject for both academics and practitioners alike.
Originally published 2000 by Routledge.
Keywords: Consumer behavior.; Consumers -- Research.; Consommateurs -- Comportement.; Consommateurs -- Recherche.; BUSINESS & ECONOMICS -- Consumer Behavior.; Consumer behavior; Consumers -- Research